Time evolution of copper defects in the mixed phase La0.5Gd0.5Ba2Cu3Oy - Guskos, N.; V. Likodimos; Calamiotou, M.; Gantis, A.; Nabialek, A.; Szymczak, H.; Wabia, M. (Radiation Effects and Defects in Solids, 1999)
XRD, magnetic and EPR studies of the mixed phase La0.5Gd0.5Ba2Cu3Oy high-Tc superconductor after prolonged (one year) `aging' at room temperature are reported. Within this time period a pronounced change of the superconducting behavior and the homogeneity of the diamagnetic shielding signal accompanied by substantial structural changes, reduction of the impurity phase BaCuO2+x and increase of the EPR spectrum's intensity of Cu2+ magnetic defects is detected. The `aging' effects are related to strain-relaxation taking place during room temperature annealing that induces the formation of Cu2+ defect centers.